A Screening Approach to Identify Clinically Actionable Variants Causing Congenital Heart Disease in Exome Data. (March 2018) - Szot, Justin O.; Cuny, Hartmut; Blue, Gillian M.; Humphreys, David T.; Ip, Eddie; Harrison, Katrina; Sholler, Gary F.; Giannoulatou, Eleni; Leo, Paul; Duncan, Emma L.; Sparrow, Duncan B.; Ho, Joshua W.K.; et al.
Abstract : Background: Congenital heart disease (CHD)—structural abnormalities of the heart that arise during embryonic development—is the most common inborn malformation, affecting ⩽1% of the population. However, currently, only a minority of cases can be explained by genetic abnormalities. The goal of this study was to identify disease-causal genetic variants in 30 families affected by CHD. Methods: Whole-exome sequencing was performed with the DNA of multiple family members. We utilized a 2-tiered whole-exome variant screening and interpretation procedure. First, we manually curated a high-confidence list of 90 genes known to cause CHD in humans, identified predicted damaging variants in genes on this list, and rated their pathogenicity using American College of Medical Genetics and Genomics-Association for Molecular Pathology guidelines. Results: In 3 families (10%), we found pathogenic variants in known CHD genes TBX5, TFAP2B, and PTPN11, explaining the cardiac lesions. Second, exomes were comprehensively analyzed to identify additional predicted damaging variants that segregate with disease in CHD candidate genes. In 10 additional families (33%), likely disease-causal variants were uncovered in PBX1, CNOT1, ZFP36L2, TEK, USP34, UPF2, KDM5A, KMT2C, TIE1, TEAD2, and FLT4 . Conclusions: The pathogenesis of CHD could be explained using our high-confidence CHD gene list for variant filtering in a subset of cases. Furthermore, our unbiased screening procedure of family exomes implicates additional genes and variants in the pathogenesis of CHD, which suggest themselves for functional validation. This 2-tiered approach provides a means of (1) identifying clinically actionable variants and (2) identifying additional disease-causal genes, both of which are essential for improving the molecular diagnosis of CHD. Abstract : Supplemental Digital Content is available in the text.